FINANCIAL TECHNOLOGY (FINTECH) IN BEHAVIOR OF RURAL COMMUNITIES IN EAST JAVA - Lilik Nurcholidah; Henny Mahmudah (Jurnal Scientia, 2023)
The presence of financial technology has greatly assisted the public in accessing financial products and the ease of conducting financial transactions with a touch of technology at hand. Moreover, seeing the current phenomenon, there is so much Covid-19 that is needed in the process of digital financial transactions. Because the strict health protocols at Century Now do not rule out the possibility of people switching to online shopping methods while simultaneously making payment transactions online. With the existence of Fintech (Financial Technology) services, it is hoped that it can help people who need to transact digital money. However, in practice, most rural people in East Java do not feel the benefits and convenience of online shopping transactions because the condition of the road infrastructure leading to the village is damaged, so that it often causes them to even have to pick up goods directly to the courier. The goods delivery service required costs more. Study of characteristics of literature review with a qualitative descriptive approach to collect and evaluate research related to the topic of fintech in Indonesia. The results of the study show that fintech has positive and negative impacts on society, but also provides benefits for society. Fintech changes people's behavior in collecting, storing and using money for transactions. For example, forget about funding for development and increase income, you can use fintech microfinancing, while Borrowing Money can use Fintech P2P Lending Services. For financial and investment planning, you can use the type of fintech Comparison of Markets and Investments.